Genologiczne zróżnicowanie akt sejmików ziemskich = Genological diversity of the acts of the land councils - Dawidziak-Kładoczna, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the article, I discuss the Sejmik discourse in the sixteenth-eighteenth century in a legal form. I distinguish in it 23 species of statements: assurance, assignment, articles, declarations, dispositions, electorate, deputies, confederacy, validation, laudation, manifestation, explanation, response of the king to the legation, ordination, power of attorney, protestation, reassurance, registrar, reprotestation, resolution , universal, admonition and nobility.
Keywords: sejmik ziemski; doba średniopolska; dyskurs sejmikowy w odmianie prawnej; gatunek wypowiedzi; land council; sejmik `s discourse in a legal form; genre of speech; 16-18 w.